Influence of full body swimsuits on competitive performance - Foster, L.; James, D.; Haake, S. (Procedia Engineering, 2012)
Swimsuit development took a massive leap forward in 2008 with the introduction of full body suits and again in 2009 with the development of the`Speedo LZR` suits with polyurethane panels and later with all polyurethane suits such as the`Arena X-Glide`. The improvements seen in swimsuit technology were accompanied by a significant rise in elite performance across the majority of the swimming events. The unprecedented numbers of World records being set at the 2008 Beijing Olympics Games and the 2009 Rome World Swimming Championships led FINA, the governing body of swimming to question the use of the swimsuits. Following the investigation, new swimsuit specifications were implemented and took effect from January 1st 2010. The new regulations effectively banned all advances in swimsuit technology. The top 25 times in each year going back to 1948 were used to assess the effects of swimsuit technology using a performance improvement index. This allowed a 5-parameter regression model to be created to quantify the size of the step changes in performance caused by the new swimsuits. The following was found: the introduction of full body swimsuits in 2000 increased performance in the men's freestyle between 0.9 and 1.4%; the introduction of polyurethane panels in 2008 increased performance by an additional 1.5-3.5%. The use of full body polyurethane suits in 2009 increased this performance further and by up to 5.5%. The women's freestyle showed similar but smaller increases in performance and the performance advantage of the suits was most evident in the sprint events. It was hypothesized that the suits reduced the cross sectional area of the swimmer and the drag coefficient CD leading to a reduction in the drag force. The increase in performance may have been reduced by the fatiguing effect of the relatively stiff swimsuits which would have impacted more in the longer events with a large number of turns.